Pengaruh Pajak Daerah dan Faktor lain terhadap Pertumbuhan Ekonomi di Pulau Jawa - Mohamad Nor Rizal; Masruri Muchtar; Pardomuan Pardomuan (Neolectura, 2022)
Financial Relations between Central Government and Local Government Law (HKPD) has been issued and will have an impact on the local government financial system. Regional taxes are one component of the regional financial system that will also be affected by the enactment of the HKPD Law. Some regional government observers are concerned that the tax provisions in the HKPD Law will slow down regional economic growth. This research aims to investigate the effect of taxes in an area on its economic growth. It uses panel data of all provinces in Java with a time period of 2016 to 2021. This study also embraces other variables such as capital expenditure, government spending, unemployment rate and inflation as control variables. The results find that the growth of tax revenue realization and the growth of government spending significantly and positively affects the economic growth of a region, while the growth of capital expenditure and inflation has a significant and negative effect on the economic growth of a region. It implies that an increase in local tax revenue tends to increase regional economic growth in the current year. In addition, regional economic growth in the current year might also increase when there is an increase in government spending and suppress inflation as well as reduce capital expenditure.